PERCEIVED HOUSEHOLD INCOME ADEQUACY AND MULTIDIMENSIONAL WELFARE AMONG OIL PALM SMALLHOLDERS: AN ISLAMIC ECONOMICS PERSPECTIVE - Vita Nurhalisa; Sitti Aisya; Nur Syamsu; Nurfitriani; M. Hidayat (Academic Bright Collaboration, 2026)
This study examines the association between perceived household income adequacy and multidimensional welfare among oil palm smallholder households in Sumber Sari Village, Bulutaba District, Pasangkayu Regency, West Sulawesi, from an Islamic economics perspective. It interprets perceived income adequacy not merely as an economic perception but as a welfare-related factor that supports falah, maslahah, family stability, and sustainable household welfare. This study employed a quantitative cross-sectional survey with a descriptive–associative approach. Data were collected from 70 oil palm smallholder households selected from a population of 230 households using simple random sampling. Perceived household income adequacy and multidimensional welfare were measured using Likert-scale questionnaire items and analyzed using descriptive statistics, Pearson correlation, and simple linear regression in RStudio. The results show a strong, positive, and statistically significant association between perceived household income adequacy and multidimensional welfare. The Pearson correlation coefficient was 0.822, and the regression coefficient was 0.816, with a p-value < 0.001. The regression model accounted for 67.6% of the variation in multidimensional welfare scores. The findings indicate that perceived income adequacy is closely related to household welfare. However, welfare policies should also strengthen education, health, productive assets, livelihood diversification, and household resilience. This study is limited to a single village and relies on self-reported Likert-scale data rather than detailed nominal income records. This study contributes village-level evidence by integrating statistical analysis of perceived income adequacy and multidimensional welfare with Islamic welfare concepts grounded in maqasid al-shari’ah.